Integrating Humanistic Leadership Practices into Modern Management (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Regardless of the advancements of humanistic  notions in management theories and applications  and the paradigm switch from an economistic  perspective to a more humanistic one, current  leadership literature still needs to be revised to  propose alternatives for a modern economic  worldview since it conforms to a mechanistic  logic. The authors primarily emphasized  highlighting the relevance of humanistic  philosophy to organizational practices by  reflecting on humanistic leadership insights  from the specific case of Tata Group, which  ensued by Tata Steel, and therefore, seek to  contribute towards a leadership model based  on humanism. The authors reviewed the  literature on Humanistic Leadership tenets  and practices to align it with the philosophy  of the Tata Group, which is typically ingrained  in Tata’s culture that shaped its underlying  prosperity and sustainability and led it to expand  holistic communal development. Humanistic  Philosophy counterbalances the growing impact  of the performance-driven managerial attitude  and, therefore, assists managers in being more  aware of the boundaries they should levy on  specific performance measures. Thus, the  authors contribute to humanistic leadership  research and open up several avenues for future  investigation into how modern leaders might  exercise humanistic leadership.
Keywords: Humanism; Humanistic Leadership; Philosophy; Humanistic Management; Tata Group; Leadership